The relationship between nesting chronology and vulnerability to hunting of dabbling ducks - Clark, Robert G; Sugden, Lawson G; Brace, R Kent; Nieman, Daniel J (Wildfowl, 1988)
Between 1980 and 1986 in south-central Saskatchewan, Canada, the percentage of broods younger than one week post-fledging when the hunting season opened was 15% (22% for Mallard), and ranged from 41% (55% Mallard) in 1983 to 4% (9% Mallard) in 1986. The associations between the relative proportion of adult females killed and both the brood index and late nesting were significant. The ratio of immature:adult ducks killed by hunters was positively associated with the late nesting index, but not with the brood index. The results suggested that, depending on the cohort examined, hunting mortality was related to breeding chronology and effort. Delaying the opening day of hunting holds promise for reducing the kill of adult hens in years when breeding effort is prolonged.